2021
DOI: 10.3390/catal11111408
|View full text |Cite
|
Sign up to set email alerts
|

Halide-Doping Effect of Strontium Cobalt Oxide Electrocatalyst and the Induced Activity for Oxygen Evolution in an Alkaline Solution

Abstract: Perovskites of strontium cobalt oxyhalides having the chemical formulae Sr2CoO4-xHx (H = F, Cl, and Br; x = 0 and 1) were prepared using a solid-phase synthesis approach and comparatively evaluated as electrocatalysts for oxygen evolution in an alkaline solution. The perovskite electrocatalyst crystal phase, surface morphology, and composition were examined by X-ray diffraction, a scanning electron microscope, and energy-dispersive X-ray (EDX) mapping. The electrochemical investigations of the oxyhalides catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“… 46 These features demonstrated the steadiness of the material toward catalytic activity for OER catalysis and confirmed the relatively higher conductivity and superficial charge-transfer process on the exposed surface of the prepared electrode. 54 However, the multistep chronopotentiometry measurements of the nickel hydroxide and I 2 -loaded nickel hydroxide electrocatalyst were not uniform throughout the experiment and the materials failed to attain the required current density. This suggests that the Ni(OH) 2 and I 2 -loaded Ni(OH) 2 electrocatalysts were not consistent during the catalytic process.…”
Section: Resultsmentioning
confidence: 99%
“… 46 These features demonstrated the steadiness of the material toward catalytic activity for OER catalysis and confirmed the relatively higher conductivity and superficial charge-transfer process on the exposed surface of the prepared electrode. 54 However, the multistep chronopotentiometry measurements of the nickel hydroxide and I 2 -loaded nickel hydroxide electrocatalyst were not uniform throughout the experiment and the materials failed to attain the required current density. This suggests that the Ni(OH) 2 and I 2 -loaded Ni(OH) 2 electrocatalysts were not consistent during the catalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the introduction of N atoms also promoted the value of (∆G *OH − ∆G *OOH ) close to the volcano center, which indicated optimized adsorption energy towards oxygen-containing intermediates during the OER process (Figure 4c,d). Additionally, halogen atoms (F, Cl, and Br) have been proven to effectively modulate the electronic structure of the matrix to improve OER performance [91][92][93][94][95].…”
Section: Metal Active Sites and Heterogeneous Non-metal Atomsmentioning
confidence: 99%
“…By exchanging anions with electronegativities and charges different from those of O 2– , such as halide ions, the electronic structure of catalysts can be modified. For example, the presence of highly electronegative fluorine has been found to create electron-deficient active sites, enhancing electronic conductivity (i.e., amorphous NiFe 2 F 4.4 O 1.8 ) or promoting surface oxygen vacancies (i.e., Sr 2 CoO 3 F), which in turn improve OER performance. Density functional theory calculations have revealed that the incorporation of chlorine, which lies at a lower orbital energy, can upshift the O p-band center and enhance the activity of cobalt-based perovskite oxychlorides (Sr 2 CoO 3 Cl, Sr 3 Co 2 O 5 Cl 2 ).…”
Section: Introductionmentioning
confidence: 99%